Balancing politics, economics and conservation: the case of the Cameroon forestry law reform - Ekoko, F. (2000)
The formulation of Cameroon's 1994 Forestry Law was influenced by the World Bank, the Government of Cameroon and French politicians, as well as by logging companies and individual Cameroonian politicians. Development objectives, direct material interests and political concerns motivated their actions. However, as the result of a flawed formulation process, conflicting interests and weak government administrative capacity, the law has not been fully implemented and may not be. An analysis of the 1994 Forestry Law suggests that the success of future policies will depend on the willingness of actors to defend their interests, the balance of power at the time, and the ability of the Executive Branch to mediate among the different interests in each case.